Effect of fertigation on the productivity of coconut - Basavaraju, T.B.; Bhagya, H.P.; Prashanth, M.; Arulraj, S. (Journal of Plantation Crops, 2014)
An experiment to study the effect of fertigation on the productivity of coconut was laid out at Horticulture Research Station, Arsikere, Karnataka during 2007-08 to 2011-12. Application of 25, 50, 75 and 100 per cent of recommended NPK through drip irrigation system was compared with the soil application of recommended NPK as well as control with no fertilizer application. Fertilizers were given through drip irrigation system throughout the year in ten equal splits at monthly interval excluding peak rainfall months of May and October. Application of 100 per cent NPK through drip irrigation recorded significantly higher number of female flowers and nut setting percentage compared to control and application of 25 per cent NPK through drip irrigation. The mean nut and copra yield per palm over five years was significantly higher with the application of 100 per cent NPK through drip irrigation compared to control and application of 25 and 50 per cent NPK through drip irrigation. However, the copra content was not significantly influenced by the fertigation treatments. Application of 75 per cent NPK through drip irrigation recorded nut and copra yield per palm on par with the application of 100 per cent NPK through drip irrigation and 100 per cent NPK through soil. The net returns and benefit-cost ratio in 75 per cent NPK through drip irrigation were also on par with the application of 100 per cent NPK through drip irrigation, but significantly higher than 100 per cent NPK through soil application. The study indicated the possibility of saving 25 per cent of the recommended fertilizers by adopting fertigation which ensures higher productivity in coconut.